杜冲이 수컷 노화쥐의 우울증에 미치는 효과 - 김호현(Ho Hyun Kim); 안상현(Sang Hyun Ahn); 박선영(Sun Young Park) (동의생리병리학회지, 2019)
In order to investigate the effects of Eucomiae Cortex extracts on the depression caused by aging, histochemistry and immunohistochemistry were performed on the hippocampus of aged rats and the following results were obtained. Experimental animals were divided into three groups as follows: 8 week old ICR male mice, Aging-elicited group (AE group) and Eucomiae Cortex treatment group (EC group) 50 week old male ICR mice were used. The control group and AE group did not take any treatment and did not restrict diets and negatives. In the EC group, 0.51g/㎏ of Eucomiae Cortex extract was dissolved in distilled water once a day for 6 months. The Eucomiae Cortex extract reduced pyramidal neuronal damage in C3 hippocampus and dentate gyrus, increased DJ-1, SHH positive responses in aged mouse hippocampus, and 8-OHdG positivity was reduced, β-endorphin positivity was reduced in aged mouse substantia nigra. Therefore, based on the above results, Eucomiae Cortex extract reduces damage of pyramidal neurons in the hippocampus caused by aging, inhibits neuronal cell death, induces proliferation and differentiation of stem cells in the hippocampus, reduces DNA damage-induced oxidative stress, so improves the reduction of hippocampus volume. It is also thought to improves depression due to aging through β-endorphin which enhances mood through the inhibition of pain. KCI Citation Count: 0